Diskursus Idealitas Batasan Konsumsi Perspektif Islam - Nasrudin (Indonesian Journal of Humanities and Social Sciences, 2022)
This article aims to describe the ideal concept of consumption in the view of Islam. The ideal concept of doing this ideal consumption is important to discuss as the basis for thinking of Muslims when consuming consumption in their daily lives. The approach used in this article is descriptive qualitative with the category of literature review, where this approach has the characteristics of collecting information and data using various types of available materials such as documents, books, magazines, and historical stories. This study finds that the ideal of consumption from an Islamic perspective is that there is an awareness in humans to spend their wealth in a balanced way, by spending it according to their basic needs. This study implies that the ideal consumption is in a balanced consumption between consumption for the benefit of the family, savings and the interests of the wider community.